SimCalc MathWorlds를 활용한 함수적 상황에서 드러나는 중학생들의 일정한 변화율에 대한 이해 - 마민영(Ma Minyoung) (Suhak gyoyukak yeon-gu (Online), 2017)
The purpose of this study is to compare and analyze middle school students' understanding of constant rate of change, in terms of observing, representing and interpreting dynamic functions in various ways using the SimCalc MathWorlds. For this purpose, parts of a class conducted for six students in the first grade of middle school were analyzed. The results suggested two implications for a class that used this program (SimCalc MathWorlds): First, we confirmed that the relationships between the two quantities that students notice in the same situation can be different. Second, the program helped students to develop a more comprehensive understanding of the meaning of the constant rate of change. The study also revealed the need to use technology in teaching and learning about functions, particularly to represent and interpret a given situation that involves the constant rate of change in various ways. Further, the results can contribute to developing contents and methods to teach functions using technology in consideration of students' different levels of understanding. 본 연구의 목적은 심칼 프로그램을 활용하여 역동적인 함수적 상황을 관찰하고, 이를 다양한 방식으로 표현하고 해석하는 과정에서 드러나는 중학생들의 일정한 변화율에 대한 이해를 비교 및 분석하는 것이다. 본 연구에서 분석된 수업은 중학교 1학년 학생 6명을 대상으로 진행된 수업 자료의 일부이다. 수업 자료를 분석한 결과, 심칼 프로그램을 활용한 수업은 다음 두 가지 의미를 갖는 것으로 드러났다. 하나는 변화율이 일정한 상황에서 학생들이 주목하는 양들 사이의 관계가 서로 다를 수 있다는 것과, 다른 하나는 학생 스스로 변량의 변화를 조정하고 그 결과를 확인하는 활동을 통해 일정한 변화율의 의미를 더 정교하게 구성하였다는 것이다. 따라서 본 연구는 함수의 교수 학습 상황에서, 특히 일정한 변화율을 포함하는 상황을 다양한 방식으로 표현하고 해석하는 활동에서 공학적 도구를 활용해야 할 필요성을 학생들과의 실제 수업에 근거하여 제시한 것으로, 학생의 이해 수준을 고려하여 공학적 도구를 활용한 함수 지도 내용과 그 방식을 계획하는 데 긍정적인 도움을 줄 것으로 사료된다.